Bank specific and macroeconomic factors on capital structure of Islamic banks in Indonesia and Malaysia - Asti, Asti; Muflih, Muhammad (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to evaluate the causality between specific banking and macroeconomic factors and their impact on capital structure, as measured by the debt-to-equity ratio in Indonesian and Malaysian Islamic Commercial Banks. Method – This study utilizes a quantitative approach with an explanatory method. The research data are secondary data obtained from the annual financial reports of BUS registered with the OJK and BNM from 2018 to 2023. The sampling technique employs non-probability sampling using the purposive sampling method, resulting in a sample of 7 Indonesian BUS and 8 Malaysian BUS. Data analysis techniques utilize panel data regression with E-Views 12 software. Findings – The results indicate that in Indonesia, liquidity has a significant impact on DER, whereas profitability and economic growth do not have a significant impact. Meanwhile, in Malaysia, profitability has a significantly negative effect on DER, while liquidity and economic growth have no significant effect. Implications – This study offers insights and reinforces the existence of the pecking order theory in Islamic banking in explaining the factors that influence capital structure. This study can help Islamic bank management in Indonesia and Malaysia control the DER ratio to mitigate the risk of default.